On the Nature of the Border: Trash Thresholds in Luis Alberto Urrea’s By the Lake of Sleeping Children - Micah McKay (Latin American Literary Review, 2021)
In this essay, I undertake an analysis of Luis Alberto Urrea’s non-fiction book By the Lake of Sleeping Children (1996), which portrays a community of trash pickers and orphans in Tijuana at a moment in which the effects of NAFTA and an increasingly militarized approach to policing the U.S.-Mexico border were taking shape. My engagement with the text combines close reading with concepts from both ecocriticism and biopolitics in order to tease out the way in which Urrea’s vignettes trouble received notions of progress, freedom, and containment. By considering the book’s deployment of two descriptive techniques for rendering the garbage dump and other spaces—one, a technique I call “time-lapse description” and the other, the insistent use of lists—I propose that the border zone that Urrea depicts is a space from which to think through the troubling and mutually-imbricated environmental, political, and economic crises that are paradoxically exceptional and exemplary of the current order of things.